The Meandrous Route of Rilpivirine in the Search for the Miraculous Drug to Treat HIV Infections - Erik De Clercq (Viruses)
Rilpivirine (RPV, R278474) was highlighted in 2005, two years after the death of Dr. Paul Janssen, as the ideal non-nucleoside reverse transcriptase inhibitor (NNRTI) to treat HIV infections. For this purpose, it was subsequently combined with tenofovir disoproxil fumarate (TDF), tenofovir alafenamide (TAF), darunavir (boosted with ritonavir or cobicistat) or dolutegravir. Its wide-spread use is thanks to its combination with cabotegravir (CAB) in the form of a long-acting intramuscular injection once per month (QM), later twice per month (Q2M), for the treatment of adults, later extended to adolescents and pregnant women, with HIV infections. The long-acting CAB plus RPV should not be administered in patients treated with rifampicin or rifabutin, patients with virological failure or patients with resistance to CAB or RPV, or patients with hepatitis B virus (HBV) infection. Long-acting CAB+RPV may lead to pain at the site of injection which would diminish over time.